Network analysis on safety culture and worker‘s behaviour : A forest of all minimum spanning trees - Djauhari, Maman A.; Sharif, Shamshuritawati; Djauhari, Hariza (IJENS Publisher, Rawalpindi, Pakistan, 2012)
In this paper safety culture and worker’s are considered, all together, as a complex system and statistically represented in the form of correlation network among their characteristics. We show that the current practice, based on a minimal spanning tree (MST), to filter the information contained in the network is not robust.A robust filter based on the forest of all possible MSTs is then proposed and used to analyze the network. For practical purpose, an algorithm will be provided to find the forest.The advantages of the proposed filter compared to the MST-based filter will be illustrated first before we use it in the case of Malaysia manufacturing industry. Some important results that will be useful for the management will be highlighted.